Chemistry of ice: Migration of ions and gases by directional freezing of water - Umer Shafique; Jamil Anwar; Munawar Ali Munawar; Waheed-uz Zaman; Rabia Rehman; Amara Dar; Muhammad Salman; Maria Saleem; Naeema Shahid; Mehwish Akram; Arooj Naseer; Nadia Jamil (Arabian Journal of Chemistry, 2016)
Redistribution of anions and cations creates an electrical imbalance in ice grown from electrolyte solutions. Movement of acidic and basic ions in cooling solutions can permanently change the pH of frozen and unfrozen parts of the system, largely. The extent of pH change associated with freezing is determined by solute concentration and the extent of cooling. In the present work, redistribution of hydrogen, hydroxyl, carbonate, and bicarbonate ions was studied during directional freezing in batch aqueous systems. Controlled freezing was employed vertically as well as radially in acidic and basic solutions. In each case, the ions substantially migrated along with moving freezing front. Conductometry and pH-metry were employed to monitor the moving ions. Besides, some other experiments were carried out with molecular gases, such as oxygen, carbon dioxide, and chlorine and an azeotropic mixture like water–ethanol. Findings can be used to understand possible changes that can occur in preserving materials by freezing.